Taking the Long Road: a Faculty Model for Incremental Change Towards Standards-based Support for Sessional Teachers in Higher Education - Savage, Julia; Pollard, Vikki (Journal of University Teaching and Learning Practice, 2016)
Despite decades of dependence on sessional teaching staff, universities in Australia and internationally still find it difficult to support the teaching work of this large, casual workforce. A significant consequence of casually-employed teaching staff is risk; sessional academics’ professional identity is compromised, quality assurance of students’ learning experiences is uncertain, and this in turn, jeopardises universities’ teaching and learning programs. These risks have existed in universities for decades, yet policies and practices that support the work of sessional staff remain inconsistent or absent. The implementation model for supporting sessional staff described in this paper, the Four Phase Model, (the 4P Model) is informed by the Sessional Staff Standards Framework (BLASST 2013), and, the Collective Impact Model, known as the CI Model (Kania & Kraner 2011). The 4P Model could help faculties systematise actions towards standards-based support for sessional staff that are inclusive professionally and contribute to the development of quality teaching and learning practice. The authors explain the thinking behind the new 4P Model, and, discuss its usefulness as a vehicle for managing incremental progress within this ‘difficult to change’ context. An evaluation of a completed trial of Phase One of the 4P Model has been included to assist faculty with implementation of all four phases of this model.